2010
DOI: 10.1111/j.1755-5922.2010.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Cardiac Valvulopathy Related to Ergot-Derived Dopamine Agonists

Abstract: SUMMARY Aims:In a previous echocardiographic prevalence study we reported a significant increase in the frequency of heart valve regurgitation in patients with Parkinson's disease taking the ergot-derived dopamine agonists pergolide and cabergoline versus controls. We followed-up our original cohort of patients to ascertain whether valvulopathy regressed after discontinuation of treatment and/or its incidence increased over time. Methods: Prospective follow-up of 101 patients treated with ergot-derived dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
8
1
1
Order By: Relevance
“…Our findings on valvular regurgitation differ from those published by Rasmussen et al [7], who didn't find any significant change in AR, MR and TR one year after EDA discontinuation, whereas a worsening of these parameters was observed in patients who continued taking the EDA. Zanettini et al observed a significant decrease of composite regurgitation score, but not of the single valve regurgitation score, in a cohort of 21 PD patients with moderate to severe (grade 3 to 4) regurgitation 22 months on average after the cessation of cabergoline and pergolide [8], whereas in our patients the improvement of the sum of regurgitations was associated to an amelioration of MR and TR. In our patients only AR showed an evolution apparently independent from the withdrawal of EDA, even though the aortic-valve was functionally less affected than the mitral and tricuspid valves.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Our findings on valvular regurgitation differ from those published by Rasmussen et al [7], who didn't find any significant change in AR, MR and TR one year after EDA discontinuation, whereas a worsening of these parameters was observed in patients who continued taking the EDA. Zanettini et al observed a significant decrease of composite regurgitation score, but not of the single valve regurgitation score, in a cohort of 21 PD patients with moderate to severe (grade 3 to 4) regurgitation 22 months on average after the cessation of cabergoline and pergolide [8], whereas in our patients the improvement of the sum of regurgitations was associated to an amelioration of MR and TR. In our patients only AR showed an evolution apparently independent from the withdrawal of EDA, even though the aortic-valve was functionally less affected than the mitral and tricuspid valves.…”
Section: Discussioncontrasting
confidence: 80%
“…Indeed, one of the limitations of these studies is the relatively short follow-up after EDA suspension, which could have caused an underestimation of the extent of regression of VHD. Our study, although conducted on a small number of PD patients, is the first to investigate the outcome of VHD associated to EDA with a follow-up duration on average more than double as compared to the longest so far reported [8]. On the other hand, a long follow-up could have some limitations.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We also used a composite scoring system derived from the sum of mitral, aortic, and tricuspid scores (value range of the composite score: 0 to 12; higher scores indicate more severe disease) as used in previous studies (14). Abnormal leaflet or cusp thickening was accepted to be present when the thickness was >5 mm.…”
Section: Echocardiographymentioning
confidence: 99%